2022
DOI: 10.1016/s1473-3099(21)00479-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic IgG seropositivity after rollout of CoronaVac and BNT162b2 COVID-19 vaccines in Chile: a sentinel surveillance study

Abstract: Background By July 14, 2021, 81•3 % of adults (aged ≥18 years) in Chile had received a first SARS-CoV-2 vaccine and 72•3% had received a second SARS-CoV-2 vaccine, with the majority of people given Sinovac's inactivated CoronaVac vaccine (75•3% of vaccines dispensed) or Pfizer-BioNTech's mRNA BNT162b2 vaccine (20•9% of vaccines dispensed). Due to the absence of simultaneous real-world data for these vaccines, we aimed to compare SARS-CoV-2 IgG positivity between vaccines using a dynamic national monitoring str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
117
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(160 citation statements)
references
References 17 publications
23
117
1
6
Order By: Relevance
“…Higher pre-boost IgG levels were associated with documented previous SARS-CoV-2 infection, and, unexpectedly, a longer interval since the second vaccine dose. However, when we assessed time since the most recent documented “virus exposure” (either by vaccine or infection), the pre-boost IgG titers correlated negatively, as expected 1921 . These findings, coupled with the high rate of documented post-CoronaVac virus breakthroughs, confirm intense SARS-CoV-2 exposure among front line heath care workers during the Delta surge in July 2021 25 .…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Higher pre-boost IgG levels were associated with documented previous SARS-CoV-2 infection, and, unexpectedly, a longer interval since the second vaccine dose. However, when we assessed time since the most recent documented “virus exposure” (either by vaccine or infection), the pre-boost IgG titers correlated negatively, as expected 1921 . These findings, coupled with the high rate of documented post-CoronaVac virus breakthroughs, confirm intense SARS-CoV-2 exposure among front line heath care workers during the Delta surge in July 2021 25 .…”
Section: Discussionmentioning
confidence: 71%
“…Real-world data from Chile reported high prevention of hospitalisation (87.5%), ICU admission (90.3%), and COVID-19-related death (86.3%) 16 . However, recent studies reported CoronaVac to have lower immunogenicity than virus vector or mRNA vaccines 18,19 , and a pronounced decrease of neutralising antibody titres within a few months 1921 , and reduced effectiveness in the elderly 22,23 . This lack of protection is concerning, especially given the rapid emergence of Omicron 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In order to estimate the proportion of immune individuals around the decoupling time, we summed the estimated number of vaccine-immunized and natural-immunized individuals. The proportion of vaccine-immunized individuals was estimated from the number of fully vaccinated individuals adjusted by the estimated vaccine effectiveness (VE) in South America [17,18], see also [19]. The number of infected people that acquired immunity through previous infection (cumulative infection) was estimated from the cumulative number of deaths assuming a constant (age adjusted) infection fatality rate (IFR) for each country (see subsection 4.1 and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Only one study using an mRNA vaccine shows preliminary results: a 95·6% efficacy of mRNA vaccine booster after 5 months. 7 Because of the pronounced decrease of NAbs titres 2 , 6 , 8 and reduced effectiveness in the older population, 9 WHO's Strategic Advisory Group of Experts on Immunization recommend a third dose of inactivated virus vaccines or a heterologous booster for people aged 60 years and older who already have received the two-dose scheme. 10…”
mentioning
confidence: 99%